Regioselective Ring-Opening of Epoxides with Thiophenols in Presence of b-Cyclodextrin in Water - Tang, Siping; Tang, Yuancheng; Xu, Zhifeng; Feng, Yonglan; Li, Junhua; Deng, Peihong (Asian Journal of Chemistry, 2016)
This paper reports a simple, mild and convenient method to synthesize b-hydroxysulfides. These b-hydroxysulfides were achieved with excellent yields (> 80 %) and high regioselectivity by ring-opening reaction of oxiranes with thiophenols in presence of the b-cyclodextrin at 30 °C in water. b-Cyclodextrin as catalyst greatly accelerated the reactions and can be recovered.